Ti3C2Tx-TiSe2 analogous heterostructure for flexible zinc ion battery. (1st July 2023) - Wen, Li; Shi, Junjie; Zhang, Qixiang; Wang, Fei; Wang, Siliang; Zhang, Shaojun; Wang, Qiang; Mao, Ke; Long, Fei; Gao, Yihua
Highlights: Analogous heterostructure (AHS) is constructed by the excellent MXene (Ti3 C2 T x ) and TiSe2 nanosheets. The composite film successfully combined the advantages of different components. DFT computations further demonstrate the excellent performance of MXene/TiSe2 composite including desirable electronic conductivity and low Zn ion migration barriers. The composite film exhibits excellent electrochemical performance and flexibility. Abstract: Exploring zinc-free anode materials is one of the effective strategies to get the zinc dendrites problem of flexible zinc ion battery (ZIB) solved. In this work, an analogous heterostructure (AHS) is constructed from the excellent MXene (Ti3 C2 T x ) and TiSe2 nanosheets. The AHS not only possesses numerous diffusion paths and Zn 2+ storage sites but also possesses a stable conductive network to accelerate charge transfer in the electrode. As a collaborative advantage, electrochemical measurement results show that MXene/TiSe2 electrodes display an excellent specific capacity of 177.9 mAh g –1 at 0.10 A g –1 and a long-term cycling stability of 77.4 % capacity retention after 400 cycles. DFT computations further demonstrate the excellent performance of MXene/TiSe2 electrodes including desirable electronic conductivity and low Zn 2+ migration barriers. The assembled flexible ZIB not only delivers a good specific capacity of 42.2 μAh cm −2 at 0.20 mA cm –2 and a competitive energy density of 37.4 μWh cm −2 but also exhibits excellent flexibility and thermostability. Furthermore, after 400 cycles at 0.60 A g −1, flexible ZIB shows a capacity retention of 73.8%. This work gives a successful attempt to design 2D layered materials as Zn metal-free anode for flexible ZIB.